Primary SMARCA4-deficient undifferentiated sarcomatoid tumor of the gastroesophageal junction - Jiahan Liu; Lingying Song; Jian Wang (Elsevier, 2020)
Background: SMARCA4-deficient thoracic sarcoma (SDTS) is a recently described high grade malignancy which occurs exclusively in the thoracic cavity. Extra-thoracic involvement has been rarely described. Case presentation: We describe here a unique case of SMARCA4-deficient undifferentiated sarcomatoid tumor (SDUST) arising primarily in the gastroesophageal junction of a 40-year-old female who is a never smoker. Histologically, the lesion showed a composite tumor composed of an undifferentiated round cell tumor and a well-differentiated spindle cell tumor, which was initially interpreted as a poorly differentiated neuroendocrine carcinoma (NEC) combined with a gastrointestinal stromal tumor (GIST) respectively. However, a comprehensive reevaluation of the submitted slides demonstrated an undifferentiated sarcomatoid tumor with striking rhabdoid morphology combined with a benign leiomyoma. Immunohistochemically, the undifferentiated sarcomatoid tumor showed a complete loss of SMARCA4 and SMARCA2, negativity for claudin-4, overexpression of SOX2, strong and diffuse expression of CD34, consistent with the phenotype of SDUST. By next-generation sequencing (NGS) analysis, tumor cells harbored TP53 gene mutation. Conclusion: This case demonstrates that SDUST may also develop in the gastrointestinal tract. Recognizing this distinct entity is important for both prognostic and therapeutic considerations.